The Impact of Klotho Gene Polymorphisms on Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review - Lindra, Derallah A; Purwaningsih, Endang; Utomo, Ahmad Rusdan H; Yunus, Faisal; Harahap, Makrup E (Indonesian Society of Respirology (ISR), 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is linked to persistent inflammation, repetitive strain, and the accelerated aging of the lungs. The Klotho gene is an anti-aging protein that protects cells from inflammation and alveolar damage in COPD patients. At least 10 mutations in the Klotho gene and single nucleotide polymorphisms (SNPs) have been identified in humans. However, the influence of these polymorphisms is not fully understood in COPD patients. This article aims to determine the influence of Klotho gene polymorphisms on COPD patients. Method: This study employs a systematic review by analyzing secondary data from scientific research articles. Data search using the Google Scholar database. Done using the terms: Polymorphism, COPD, and Alpha Klotho gene. Results: Four studies were selected for systematic review. Three studies indicate that Klotho gene polymorphisms can cause alveolar destruction, accelerating emphysema occurrence. There is a relationship between Klotho gene polymorphisms and BMI but not with disease severity parameters. Conclusion: This review indicates that Klotho gene polymorphisms may accelerate emphysema development in COPD patients. There is a relationship between klotho gene polymorphisms and BMI but not with disease severity parameters.